ECHO CHAMBERS DI DUNIA MAYA: TANTANGAN BARU KOMUNIKASI ANTAR UMAT BERAGAMA - Yuangga Kurnia Yahya; Umi Mahmudah (Religi: Jurnal Studi Agama-agama, 2019)
This article tries to see a phenomenon called Echo Chambers through the perspective of Stella Ting-Toomey’s Intercultural Communication Theory. This study shows that the development of social media was also followed by the shadow of Echo Chambers. The tendency to isolate oneself and associate with those who understand one another will create separate spaces between one religion and another. As a result, communication which is an effort to eliminate the polarization of the differences between "Us" and "The Others" is precisely the way to form an exclusivism in cyberspace. Among the efforts to anticipate the emergence of a gap is to create melting-pot spaces in the real world. Counter narrative also needs to be built to open these exclusive barriers. Muslim scholars sought to introduce the importance of communication in achieving the harmony in community. Some Ulama have also explained the role and function of communication in achieving the goals of the ummah, as well as trying to provide an Islamic perspective regarding communication behavior. More important, is to create a person who is a wise, open user of social media and uses epoche in looking at the world outside.